The Integration of Metabolomic and Proteomic Analyses Revealed Alterations in Inflammatory-Related Protein Metabolites in Endothelial Progenitor Cells Subjected to Oscillatory Shear Stress - Yu, Jie; Fu, Jie; Zhang, Xiaoyun; Cui, Xiaodong; Cheng, Min (Frontiers in Physiology, 2022)
Background: Endothelial progenitor cells (EPCs) play essential roles in vascular repair. Our previous study suggests oscillatory shear stress () would lead EPCs transdifferention into the mesenchymal cell that aggravates pathological vascular remodeling.The primary purpose of this study was to apply OSS in vitro in EPCs and then explore proteins, metabolites, and the protein-metabolite network of EPCs. Methods: EPCs were kept in static or treated with OSS. For OSS treatment , the Flexcell STR-4000 parallel plate flow system was used to simulate OSS for 12 h. Subsequently, an untargeted metabolomic LC/MS analysis and a TMT-labelled quantitative proteomic analysis were performed. Results: A total of 4699 differentially expressed proteins (DEPs) were identified, among which 73 differentially expressed proteins were potentially meaningful (P<0.05), with 66 upregulated and 7 down-regulated expressions. There were 5664 differential metabolites (DEMs), of which 401 DEMs with biologically potential marker significance (VIP>1, P<0.05), of which 137 were upregulated and 264 were down-regulated. The Prison correlation analysis of DEPs and DEMs was performed, and the combined DEPs–DEMs pathway analyses of the KGLM database show 39 pathways. Among the DEPs, including the Phosphoserine phosphatase (PSPH), Prostaglandin E synthase 3 (PTGES3), Glutamate--cysteine ligase regulatory subunit (GCLM), Transaldolase (TALDO1), Isocitrate dehydrogenase 1 (IDH1) and Glutathione S-transferase omega-1 (GSTO1), which are significantly enriched in the citric acid cycle (TCA cycle) and fatty acid metabolic pathways, promoting glycolysis and upregulation of fatty acid synthesis. Moreover, we screened the 6 DEPs with the highest correlation with DEMs for predicting the onset of early AS and performed qPCR to validate them. Conclusion: The comprehensive analysis reveals the following main changes in EPCs after the OSS treatment: dysregulation of glutamate and glycine metabolism and their transport/catabolic related proteins. Disorders of fatty acid and glycerophospholipid metabolism accompanied by alterations in the corresponding metabolic enzymes; Elevated expression of glucose metabolism.